Penerapan Model Pembelajaran Kooperatif Tipe Scramble Berbantuan Media Kartu Kata Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Sekolah Dasar - Annisa Azizah; Fitri Nuraeni (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Early reading learning is important in the learning process, and the lack of early reading learning is a problem addressed in this study. The purpose of this research is to determine the process of implementing the scramble cooperative learning model and to improve the early reading learing of Grade 1 students at SDN 1 Cisereuh through the implementation of the scramble cooperative learning model assisted by word card media. This research is a Classroom Action Research conducted in cycles, with 28 students as the research subjects, consisting of 16 male students and 12 female students. The data collection techniques used in this research are observation, interviews, and initial reading test sheets. Student observation and interview sheets are used to determine the learning process and student activities during the learning activities. Meanwhile, teacher observation sheets are used to determine the teacher's activities during the implementation of the cooperative learning model assisted by word card media to improve the early reading leraning of elementary school students. The results of the research are as follows: a) In cycle I, the teacher's activity obtained an average score 71,4% and increased in cycle II to 100%; b) The activities of Grade 1C SDN Cisereuh students improved positively after the implementation of cooperative learning model assisted by word card media. The increase in student activity in cycle I with an average of 64.2% and in cycle II, it increased with an average of 92.85%; c) The implementation of the scramble cooperative learning model assisted by word card media is proven to improve the early redaing learning of students, with an average score of 86.07 in the good category in cycle I. In cycle II, the average score is 92.85 in the excellent category, which increased by 3.93 points.